Climate Finance and Sustainable Development in Nigeria’s Lake Chad Basin: A Case Study of Borno State - Mohammed Saleh; Muhammad Shettima Daluma (CV. Kalimasada Group, 2026)
The Lake Chad Basin, spanning Cameroon, Chad, Niger, and Nigeria, supports millions of people through fishing, agriculture, and pastoralism. However, the lake has shrunk by about 90% since the 1960s, causing water scarcity, food insecurity, and displacement. These challenges are further intensified by climate change and regional insecurity, making climate finance essential for strengthening resilience and sustainable development. This study aims to analyze climate finance flows, challenges, and impacts in the Lake Chad Basin, focusing on Borno State, Nigeria. The research applies a qualitative case study approach based on literature review, analysis of climate finance project data, and stakeholder insights. The findings show that Nigeria mobilized about 4.9 billion in climate finance between 2015 and 2021, which remains far below the estimated financing needs. Most funding comes from international sources, while implementation at the local level faces institutional and security constraints. Some programs have improved agricultural productivity and livelihoods, but governance and equity challenges persist. Strengthening local capacity, community participation, and transparent financing mechanisms is essential to ensure climate finance effectively supports resilience and poverty reduction in the region.